Growth patterns of the nasolabial region following unilateral cleft lip primary repair - Xu, Yulang; Zeng, Ni; Li, Jingtao; Zheng, Qian; Shi, Bing (Frontiers in Pediatrics, 2023)
Surgical correction is the optimal way to repair congenital cleft lip. Patients often undergo initial surgical treatment at an early age and achieve an acceptable outcome. However, satisfactions will be decreased in later of life as the growth and development of patients will inevitably cause changes of the long-term outcomes especially in nasolabial region. Therefore, it is important for surgeons to understand the nasolabial development after primary treatment and trim surgical techniques appropriately. This review is focusing on the growth patterns of the nasolabial region after primary repair, so as to provide references for operative strategy.